The Nurse Workforce in the Eastern Caribbean : Meeting the Challenges of Noncommunicable Diseases - Carpio, Carmen; Fuller-Wimbush, Danielle (World Bank, Washington, DC, 2016)
The health workforce must be able to cope with shifts in the pattern of causes of death and disease that are being seen worldwide—particularly with the rise in noncommunicable diseases (NCDs). This requires health personnel to have a set of skills and competencies that can adapt to meet the population’s growing and changing health needs.